The main risks of fad diets and the importance of proper nutritional guidance (Research, Society and Development, 2022)
The search for the ideal weight and the difficulty of achieving it in a short term, made fad diets gain space both in the media and in society because of the erroneous promise of aesthetic results in a short period. The purpose of this article is to present the risks associated with fad diets and the importance of monitoring the nutritionist during and after the weight loss process. The methodology applied in this work is the integrative literature review, which was based on the following research platforms: LILACS, SciELO, Pubmed and Google Scholar. Inclusion criteria were applied that delimited the period of analyzed publications (2017-2022), the accepted research methodologies (bibliographic, reviews and case studies). After these delimitations, it was possible to discuss 12 articles that present the relevance of adequate nutritional guidance during and after the weight loss process, as well as the harms of starting and continuing a fad diet on your own. In this way, following fad diets without nutritional guidance increases the incidence of eating disorders, property imbalance important for the functioning of the human body, as well as nutritional deficiency adequate for human quality of life.